Pelanggaran Etika Pariwara: Kontroversi Iklan Rabbani tentang Busana Wanita dan Pelecehan Seksual - Andin Nabil Hernawan; Didi Suwandi; Muhammad Fritzy; Daniel Handoko (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
In early January 2023, the hijab and Muslim fashion brand Rabbani faced serious controversy after releasing an advertisement deemed to violate advertising ethics in Indonesia. The advertisement stated that women's attire is the cause of sexual harassment, a claim that was strongly refuted by the National Commission on Violence Against Women (Komnas Perempuan). Additionally, Rabbani sparked public outrage with a billboard featuring an image of a goat wearing a hijab. This study aims to analyze the ethical violations in Rabbani's advertising, the public's response to the advertisement, and the long-term impact on the brand's reputation. A qualitative research method was employed to gain in-depth insights into consumer perceptions and the social and cultural implications of this controversial advertisement. The findings indicate that ethical violations in advertising can reinforce negative stereotypes, damage brand reputation, and trigger significant public backlash. These results underscore the importance of adhering to advertising ethics to maintain a brand's integrity and credibility.